(3GdfcJ hGdCeGdj aj GdfbV Ydi GdZRGdis - (3CHhYHO Gddg eMeO Hf GdaNGQ Hf Nda GdGdHjQj GdNhdGfj GdHjQjs
(3ChdgG (B:s
(3hHeYdheg hcGdHjGV GdPi gh HjGP dfaSg hdZjQg hjLhR Cf jchf GdEOQGc eOQckG ai ZjQ eMdg s
(3BNQgG (B:s
(3fcJg CNQi hgj bhd GdfHi Udi Gddg Ydjg hSde (B( (3ef JQc GdLeYI KdGK eQGJ ef ZjQ YPQ hdG YdI WHY Gddg Ydi bdHg (B) (3bHd GdUdGI EjeGfkG MJi JbOM s
(3fSNI YJjbIs
(3dYdgG cJHJ ai MjGI GdeDdas
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdESdGejs